2021
DOI: 10.1039/d1sc00755f
|View full text |Cite
|
Sign up to set email alerts
|

Controllable stereoinversion in DNA-catalyzed olefin cyclopropanation via cofactor modification

Abstract: Cofactor modification in a DNA-catalyzed olefin cyclopropanation reaction enables controllable stereoinversion and achieves enantioselectivities of up to +91% and −72% eetrans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Consequently, the topology at these sites is critical when treating the structure as a chiral ligand, as this is the environment in which the reaction occurs. G4 structures has also been designed for artificial metalloenzymes based on DNA metalloenzymes. , Recently, Li et al developed a series of reactions involving G4 metalloenzyme catalysis, employing G4 and Fe porphyrin as promising biocatalysts for olefin cyclopropanation (Figure A) …”
Section: General Character and Applications Of G-quadruplexmentioning
confidence: 99%
“…Consequently, the topology at these sites is critical when treating the structure as a chiral ligand, as this is the environment in which the reaction occurs. G4 structures has also been designed for artificial metalloenzymes based on DNA metalloenzymes. , Recently, Li et al developed a series of reactions involving G4 metalloenzyme catalysis, employing G4 and Fe porphyrin as promising biocatalysts for olefin cyclopropanation (Figure A) …”
Section: General Character and Applications Of G-quadruplexmentioning
confidence: 99%
“…The recent advances in supramolecular DNA hybrid catalysts clearly demonstrated the capacity of DNA as a chiral source and support the use of DNA-based biocatalysts in a much broader spectrum of reactions. Despite the ongoing efforts to gain mechanistic insight by inferring the active site from spectroscopic analysis, [37,47] there were still issues that could not be answered clearly. For instance, it was difficult to accurately represent the exact position and the binding mode of metalligand complexes on DNA.…”
Section: Modular Dna Hybrid Catalysts By Direct Incorporation Of Meta...mentioning
confidence: 99%
“…The remarkable catalytic ability of G4 scaffolds combined with iron-porphyrins (Fe-TMPyP4) has been reported. [36,37] Inspired by the first example of G4 DNA-based hybrid catalysts for enantioselective cyclopropanation, [38] Li and colleagues improved the catalyst performance by further optimization. The diastereomeric cyclopropanes have been synthesized from styrene derivatives 4a-c and ethyl diazoacetate (EDA, 5a-c) (Scheme 2).…”
Section: The Advent Of Dna-based Hybrid Catalysts: Supramolecular-ass...mentioning
confidence: 99%
“…[14,15] Indeed, it was shown that the hybrid formed with a G-4 and the natural peroxidase cofactor hemin (iron(III) chloroprotoporphyrin IX), with the porphyrin group stacked on top of apical quartets, was able to mimic the natural peroxidase upon addition of H 2 O 2 . [16][17][18] It was also found that this combination could catalyze oxygen transfer reactions but without any enantioselectivity [19] (whereas it is able to catalyze asymmetric cyclopropanation reactions [20,21] ).…”
Section: Introductionmentioning
confidence: 99%